2022
DOI: 10.1002/eat.23696
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorder Examination‐Questionnaire: Evaluating factor structures and establishing measurement invariance with Asian/Hawaiian/Pacific Islander, Black, and White American college men

Abstract: Objective: This study evaluated the factor structure and invariance of the Eating Disorder Examination-Questionnaire (EDE-Q) in a sample of Asian/Hawaiian/Pacific Islander (n = 163), Black (n = 155), and White (n = 367) American university men.Method: Twelve different EDE-Q factor structures reported in the literature were evaluated using multi-group confirmatory factor analyses, and measurement invariance assessed.Results: A respecified four-factor structure proposed by Parker et al. (2016) showed superior fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 94 publications
(190 reference statements)
0
14
0
Order By: Relevance
“…The Weight Concern and Shape Concern subscales have been found to be highly correlated, and several studies in the current review generated latent structures through EFA whereby items of these subscales were considered under a “Weight and Shape Concern” subscale (e.g., Carey et al, 2019; Darcy et al, 2013; White et al, 2014). There was mixed evidence for the presence of a “Global” index of eating pathology, with several studies (Friborg et al, 2013; Klimek et al, 2021; Rand‐Giovannetti et al, 2020) generating conflicting findings regarding higher‐order models, suggesting that interpretation of the Global score might remain cautious, particularly in non‐female or ethnic minority groups (Goel, Burnette et al, 2022). Similarly, whilst some studies found that a one‐factor solution emerged from EFA (e.g., Peterson et al, 2020), others failed to find support using CFA (e.g., Calugi et al, 2017; Penelo et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Weight Concern and Shape Concern subscales have been found to be highly correlated, and several studies in the current review generated latent structures through EFA whereby items of these subscales were considered under a “Weight and Shape Concern” subscale (e.g., Carey et al, 2019; Darcy et al, 2013; White et al, 2014). There was mixed evidence for the presence of a “Global” index of eating pathology, with several studies (Friborg et al, 2013; Klimek et al, 2021; Rand‐Giovannetti et al, 2020) generating conflicting findings regarding higher‐order models, suggesting that interpretation of the Global score might remain cautious, particularly in non‐female or ethnic minority groups (Goel, Burnette et al, 2022). Similarly, whilst some studies found that a one‐factor solution emerged from EFA (e.g., Peterson et al, 2020), others failed to find support using CFA (e.g., Calugi et al, 2017; Penelo et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Using a Spanish translation of the EDE-Q in college women, Villarroel et al (2011) reported "satisfactory" fit, noting that they The Weight Concern and Shape Concern subscales have been found to be highly correlated, and several studies in the current review generated latent structures through EFA whereby items of these subscales were considered under a "Weight and Shape Concern" subscale (e.g., Carey et al, 2019;Darcy et al, 2013;White et al, 2014). There was mixed evidence for the presence of a "Global" index of eating pathology, with several studies (Friborg et al, 2013;Klimek et al, 2021;Rand-Giovannetti et al, 2020) generating conflicting findings regarding higher-order models, suggesting that interpretation of the Global score might remain cautious, particularly in non-female or ethnic minority groups (Goel, Burnette et al, 2022).…”
Section: Latent Structuresmentioning
confidence: 90%
See 3 more Smart Citations